HAK REPRODUKSI PEREMPUAN dalam Perspektif Syariat Islam - La Ode Angga (UIN K.H. Abdurrahman Wahid Pekalongan, 2011)
Islam as Din has more authority to function to save and liberate people from tyranny-the tyranny of other human beings. The Qurâ€™an mentions this function as â€œyukhrijuhum min al zhulumat ila Al-Nurâ€ (removing people from darkness to light). View of human equality, men and women in the Qurâ€™an include aspects of spirituality, intellect and sexuality as well as all other practical life activities. About the relationship of sexuality, the Qurâ€™an states: â€œand they (women) have rights comparable to their obligationsâ€. Ibn Abbas, a prominent companion of the Prophet, commenting on this verse by saying: â€œI like dressing up for my wife as I like her dress up for meâ€. Another verse also says: â€œthey (women) are a garment for you and you are garments for themâ€.